Absorption and Sinking Speed of Artocarpus Stems Rope (Artocarpus sp.) and Carex Grass Rope (Carex sp.) in Freshwater and Seawater - Amraini Fitri; Nofrizal Nofrizal; Romie Jhonnerie; Fauzan Ramadhan (Jurnal Perikanan dan Kelautan, 2022)
Artocarpus stems (Artocarpus sp.) and Carex grass (Carex sp.) have not been applied to fishing gear materials. The fibers produced made into a rope, where this rope is used to absorption and sinking speed test in fresh water and sea water.The absorption of Artocarpus stems rope was 320.30% and 282,60% in fresh water and sea water. Meanwhile for sinking speed have a 5,78 cm/s and 5,08 cm/s for fresh water and sea water. For the Carex grass rope, the absorption in fresh water and sea water was 287,67% and 218,02%. Sinking speed value 2,97 cm/s and 2,67 cm/s for fresh water and sea water. The value of absorption and sinking speed in fresh water is higher than in sea water for both types of rope